THE EFFECT OF ENERGY CONSUMPTION, FIXED CAPITAL AND LABOR COST ON MANUFACTURING OUTPUT IN INDONESIA - Triyana Iftasari (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to determine the effect of energy consumption, fixed capital and labor cost on manufacturing output in Indonesia in 2017-2019. This research is associative research and the method used is a quantitative approach. The data used in this study is panel data collected through documentation techniques. To analyze the data in this study using regression analysis and assistance in the form of an application Econometric Views (Eviews 12). The test results show that energy consumption has a positive effect on manufacturing output, fixed capital has a positive effect on manufacturing output and labor costs have a positive effect on manufacturing output. In addition, simultaneously, energy consumption, fixed capital and labor costs have a positive effect on manufacturing output. Coefficient determination test of the independent variable in this study shows the effect of 81.16% on manufacturing output. Meanwhile, another 18.84% is influenced by factors outside this research